The Convergence of AI and Microbiology: Unprecedented Prospects for Precision Diagnosis and Therapy - Al-Hadidi, Enass; Dawood, Ali (Annals of Mechnikov’s Institute, 2025)
The transformation of microbiology research by artificial intelligence (AI) became possible through its optimization of microbial system analysis and global health research work. AI enables machine learning algorithms to undertake genome-based sequencing functions and disease identification activities as well as drug development capabilities which deliver biochemical research with exceptional speed and exactness. These developments establish basic instruments that help both resistance management and diagnostic enhancement alongside individual therapeutic innovation. The practical implementations from artificial intelligence include both vaccine development and strains engineering through microbial modifications which serve manufacturing development and environmental requirements and predictive systems for natural ecosystem variability. The functional abilities transform healthcare operations while developing agricultural practices and sustainability solutions which operate across global platforms. Nevertheless, the integration of AI technology into microbiology workfares various technical barriers. AI system use requires fixing data quality issues combined with algorithm clarity and unrestricted access and responsible management of all ethical questions. Moving forward with artificial intelligence integration in microbiology requires collaborative work between microbiology experts together with computational scientists and staff who generate governmental policies. AI development in microbiology will lead to remarkable progress through personalized therapeutic medicine generated from microbiome analysis as well as stronger outbreak detection abilities. Microbiological research development will experience a transformation because innovative collaboration will open new opportunities toward better human and environmental advancement and hope.